Animal Totems and its Representation in Philip Pullman’s Northern Lights - CINDI AMANDA DISTIA KUSUMA WARDANI (LITERA KULTURA : Journal of Literary and Cultural Studies, 2019)
This study uses descriptive qualitative method which focusing on the literary work in the novel and interpretation on the analysis. The main data is taken from one of Phillip Pullman‟s trilogy entitled Northern Lights. The main focus of this study is the three main characters and their daemons of the novel named Lyra Belacqua, Lord Azriel and Marisa Coulter then their daemons named Pantailamon, Stelmaria, and Ozymandias. This study aims to analyze how the three main characters and their daemons lead their life to Totemism and the representation of the animal totems toward human‟s personality trait based on the three main characters which already stated in the research questions. Totems are symbols or representations of human‟s affiliations with, and/or categorizations of, animals, plants and inanimate objects. Totemism is related to fundamental human belief systems based on totems. Investigating totems and totemism psychologically is a unique way to explore human minds. The theory from Wundt and Freud for definition of the term totemism and the representation of animal totems toward characters‟ personality using Carl Jung about four basic psychological functions are applied to reveal the problems. This analysis shows how the three main characters with their daemons lead their life to totemism by revealing the three characters‟ activites, behavioural and way to respond something to a certain circumtances. Beside that, the representation of the three characters in term of their personality traits can be identified whether they belong to extrovert or introvert by finding the similarities between the daemon and the character according to the meaning of each animal totems and four basic psychological functions. Keywords: Animal Totem, Totemism, and Personality TraitPenelitian ini menggunakan metode penelitian deskriptif kualitatif yang berfokus pada karya sastra dalam novel dan interpretasi dalam analisis. Data utama diambil dari salah satu trilogi Philip Pullman yang berjudul Northern Lights. Fokus utama pada penelitian ini adalah ketiga karakter utama yang bernama Lyra Belacqua, Lord Azriel and Marisa Coulter dan daemon mereka yang bernama Pantailamon, Stelmaria, dan Ozymandias. Penelitian ini bertujuan untuk menganalisis bagaimana ketiga karakter utama dan daemon mereka mengarah hidupnya pada totemisme dan representasi dari totem binatang terhadap kepribadian manusia seperti yang telah dinyatakan dalam rumusan masalah. Totem adalah sebuah simbol atau representasi dari afiliasi manusia atau kategori dari hewan, tumbuhan dan objek mati. Totemisme berhubungan dengan kepercayaan mendasar manusia berdasarkan totem. Menginvestigasi totem dan psikologi totemisme adalah hal yang unik untuk di jelajahi dalam pemikiran manusia. Teori dari Wundt dan Freud untuk gambaran definisi dari totemisme dan representasi dari totem binatang terhadap kepribadian karakter menggunakan teori Carl Jung mengenai empat fungsi psikologis dasar ini diterapkan untuk mengungkapkan masalah yang ada. Analysis mengacu pada bagaimana ketiga karakter utama dan daemon mereka mengarahnya pada totemisme dengan mengungkapkan kegiatan, perilaku, dan dalam menanggapi sesuatu di keadaan tertentu. Selain itu, representasi dari ketiga karakter perihal sifat kepribadian mereka dapat dikategorikan sebagai ekstrovert atau introvert dengan menemukan persamaan diantara daemon dan karakter berdasarkan arti dari masing-masing totem binatang dan empat fungsi psikologis dasar. Kata Kunci: Totem Binatang, Totemisme, dan Sifat Kepribadian